Classification of betel leaves (Piper betle) from 15 ethnics in eastern Indonesia based on phytochemicals fingerprint analysis - Dimas Andrianto; Husnawati; Suci Hermita; Sari Haryanti (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Andrianto D, Husnawati, Hermita S, Haryanti S. 2020. Classification of betel leaves (Piper betle) from 15 ethnics in eastern Indonesia based on phytochemicals fingerprint analysis. Biodiversitas 21: 252-257. Betel (Piper betle Linn), also called Golden Heart of Nature, is often used as traditional medicine. Nonetheless, betel plants originated from different places contains different phytochemicals profile, resulting in different utilization across ethnics. The research aimed to classify betel leaves from eastern Indonesia origins based on phytochemical profiles. In this study, the phytochemical profiles of 69 betel leave samples from 15 ethnics in eastern Indonesia were obtained using High-Performance Liquid Chromatography (HPLC) fingerprint analysis. This data was then used to classify the betel leaves samples using Principal Component Analysis (PCA). The results of the analysis show that the betel leaves from Eastern Indonesia can be divided into three clusters. Cluster 1 consisted of betel leaves originated from two ethnics, namely Komoro and Greri, from Papua, while Cluster 2 consisted of those originated of two ethnics, namely Sumber Baba and Demta, both were also from Papua. Cluster 3 consisted of betel leaves originated 11 ethnics, namely Asilulu (Maluku), Balesang (Central Sulawesi), Bungku (Central Sulawesi), Mulong Kuni (Central Sulawesi), Saluan (Central Sulawesi), Tialo (Central Sulawesi), Tolage (Central Sulawesi), Gebe (North Maluku), Makian (North Maluku), Mey Brat (West Papua) and Waigeo (West Papua). The location of P. betle plantation in this research accounts for clusterization of samples, Papua island give the highest biodiversity because we can find all the three cluster in Papua island.